Zahteve glede uspešnosti vratark v ekipnem rokometu - Weber, J.; van Maanen-Coppens, L.; Wegner, M. (Kinesiologia Slovenica, 2018)
Success in competitive sports is limited by constitutional, conditional, coordinative, technical, psychological and tactical factors. These factors differ by position in team handball, and the differences have yet to be sufficiently specified. Especially for female goalkeepers, the demands remain unclear. Testing for goalkeeper performance demands in handball reveals that previous values do not match those of field players. Still, the goalkeepers tested played in top leagues and apparently met game standards for their position. Consequently, the core demands of the goalkeeper position must be clarified, as well as how goalkeepers differ from field players. To this end, 654 female handball players from German leagues of all performance levels were tested for the above-mentioned factors. Each player\'s handballspecific expertise was used as the independent variable while the performance differences between positions were seen as dependent variables, as was goalkeeper performance. There were significant differences between goalkeeper and field player performance. Core position demands for goalkeepers were experience ("anticipation expertise"), ambidexterity, low action/state orientation after malperformance and the 30m sprint (fastest of two attempts). Results also suggest that goalkeepers should orient their performance on that of field players for the following factors; sit-ups, reaction test, jump & reach, 10 and 20m sprint, Cooper test, throwing speed, wall passing, slalom dribbling, tactics test, hope for success, net hope, selfoptimization, self-impediment, lack of activation, and action/state orientation after malperformance. Coaches should implement specialized training for goalkeepers.